Procesos didácticos de la lectura y la comprensión lectora en niños de la institución educativa inicial N°62791 Balsapuerto 2024 - Baneo Rucoba, Zaira Veronica (2025)
The objective of this research is to analyze the relationship between the application of reading didactic processes and the level of reading comprehension in children from the Initial Educational Institution N°62791 Balsapuerto during the year 2024. This study adopts a quantitative approach and is classified as relational research, non-experimental, with transactional and correlational designs. The study population consists of all the children from this institution, totaling 45 participants. For data collection, the observation technique was used, implementing an observation guide as an instrument, which underwent rigorous validity and reliability testing. The validity was assessed by three experts in the field, ensuring the instrument's relevance. The results obtained through the Spearman correlation coefficient were 0.743, indicating a strong positive correlation between the two variables under study. Additionally, a bilateral significance of 0.05 reinforces this connection, allowing us to conclude that there is a clear relationship between reading didactic processes and reading comprehension in the analyzed group. Therefore, the formulated research hypothesis is accepted.